2014
DOI: 10.1590/1413-8050/ea440
|View full text |Cite
|
Sign up to set email alerts
|

Custos de bem-estar da inflação no Brasil pós-real

Abstract: ResumoEste trabalho investiga o comportamento da demanda por moeda no Brasil de forma a derivar os custos de bem-estar da inflação pós-Plano Real. Os resultados, para um período de dezessete anos, corroboram a forma funcional log-log que mostra significativos ganhos de bem-estar relativos aos custos sociais anteriores ao Plano Real. Para uma inflação de aproximadamente 4, 5% a.a., tem-se custo de bem-estar entre 0, 15 e 0, 20% da renda. Conclui-se, como esperado, que o país deve direcionar suas políticas para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The welfare cost, in its turn, has a strong and positive correlation with the inflation rate, as we can see in Figure 13. Kumar (2014) concluded that Cagan's model is more adequate to the Indian economy, our results show that Meltzer's model is a better fit for Brazil in the time period under study, as Caetano et al (2014) also did.…”
Section: Welfare Cost Of Inflationsupporting
confidence: 70%
See 4 more Smart Citations
“…The welfare cost, in its turn, has a strong and positive correlation with the inflation rate, as we can see in Figure 13. Kumar (2014) concluded that Cagan's model is more adequate to the Indian economy, our results show that Meltzer's model is a better fit for Brazil in the time period under study, as Caetano et al (2014) also did.…”
Section: Welfare Cost Of Inflationsupporting
confidence: 70%
“…The elasticity estimations, however, differ greatly between the two works. As we can see in Figure 15, most of the values from our model lie below the lowest estimate of 0.423 from Caetano et al (2014), for both the Kalman filter and the time varying cointegration methods.…”
Section: Welfare Cost Of Inflationmentioning
confidence: 67%
See 3 more Smart Citations